Farmers’ adoption of smart agricultural technologies for black soil conservation and utilization in China: the driving factors and its mechanism - Yu, Jiaping; Li, Jing; Lo, Kevin; Huang, Shanlin; Li, Yiqi; Zhao, Zixin (Frontiers in Sustainable Food Systems, 2025)
Smart agriculture can mitigate the degradation of black soil organic matter to ensure global food security and promote sustainable agricultural development. However, the adoption of smart agricultural technology for black soil conservation and utilization is poorly understood. This study analyzes the influence mechanisms affecting farmers’ adoption intentions of one such technology, variable fertilization. We develop a structural equation model by combining the Technology Acceptance Model (TAM), Perceived Value Theory (PVT), and external factors with data from 354 farmers in Youyi State farm in the Sanjiang Plain Area, China. The results revealed that social influence (SI) was the most significant determinant of farmers’ adoption intentions (AI), emphasizing the critical role of social networks, particularly information from experienced demonstration households, in shaping decisions. Additionally, both the perceived usefulness (PU) and perceived ease of use (PEOU) of variable fertilization technology (VFT) significantly and positively influenced AI. Among these, PEOU demonstrated a greater overall impact than PU. We propose strategies for demand-driven, incentive-based, and technical support mechanisms to facilitate the adoption of VFT and conclude with recommendations to promote black soil conservation and utilization technologies among farmers.